HUBUNGAN KRONOTIPE DENGAN DERAJAT NYERI DISMENORE PADA REMAJA PUTRI - Ardina, Safira Cindra; Widyaningsih, Vitri; Lestari, Anik (Media Penelitian dan Pengembangan Kesehatan, 2023)
Dysmenorrhea is one of the most common menstrual disorders in young women. The prevalence of dysmenorrhea in adolescent girls in Indonesia ranges from 16.8-81%. Girls with dysmenorrhea symptoms have a higher risk of decreased activity, experiencing hip strain, back pain, headaches, and fatigue. In school children, it can interfere with learning activities and concentration, causing academic decline. Dysmenorrhea is influenced by several factors from daily activities and habits. Activity can affect a person's sleep and wake schedule. The difference in sleep and activity schedules of each person is known as kronotipe. The study aimed to determine the relationship between kronotipe and the degree of dysmenorrhea pain in adolescent girls at SMKN 1 Doko Blitar. The research was conducted in August-September 2021. The population of the study was 60 students of SMK 1 Doko in Blitar district aged 15-18 years old, non-smoking, and who want to join this study. The research plan is a cross-sectional study using MEQ-SA (Morningness-Eveningness Questionnaire Self-Assessment Version), and the dysmenorrhea questionnaire. Data analysis uses the chi-square test. The result of chi-square test showed a significant correlation between the kronotipe with the degree of dysmenorrhea pain (p-value= 0,000). There is a significant relationship between chronotype and the degree of dysmenorrhea pain. Adolescent girls need to set a regular sleep schedule to have an appropriate chronotype to reduce dysmenorrhea pain during menstruation.